Mutinous colonialism: navigating self-other dichotomy in Octavia Butler's Survivor - Al Ogaili, Thamer Amer Jubouri; Babaee, Ruzbeh (Australian International Academic Centre, 2015)
This article examines the self-other relationship in Octavia Butler’s novel Survivor (1978). This relationship incarnates the colonial powers brought about the missionaries in their early advent in the fictional place known as “Earth”. This place is the foundational setting where the main events take place. The study focuses on the representation of this setting in terms of colonial affiliation. The missionaries are encountered by the natives known as “Kohn” who resist their discrimination practices. Alanna, the protagonist, will be the main focus of the study. She represents the severe dichotomy between the colonial invasion and the proper human attributes. She is a native of Kohn, but she is adopted by the missionaries’ leader. Such adoption is highlighted by the use of two main concepts. The first of these is Edward Said’s concept of self-other relationship. The second concept is Homi Bhabah’s ambivalence. These concepts unravel the suppressed voices in Survivor. They will be analyzed within the colonial infringement in the novel’s narrative structure.